Hersilia aadi Pravalikha, Srinivasulu & Srinivasulu, 2014 a junior synonym of Hersilia savignyi Lucas, 1836 (Araneae: Hersiliidae) - Caleb, John T.d.; Pravalikha, G.b.; Johnson, Benaiah Ebenezer; Manyu, Mitemlu; Mungkung, Soreiphy; Mathai, Manu Thomas (Zootaxa, 2017)
The genus Hersilia was established by Audouin in 1826 with H. caudata Audouin, 1826 as the type species. It is the most speciose hersiliid genus presently comprising 79 described species worldwide (World Spider Catalog 2017, version 18). There are seven species known from India: H. aadi Pravalikha, Srinivasulu & Srinivasulu, 2014, H. longivulva Sen et al., 2010, H. orvakalensis Javed et al., 2010, H. savignyi Lucas, 1836, H. striata Wang & Yin, 1985, H. sumatrana (Thorell, 1890), H. tibialis Baehr & Baehr, 1993. This paper is based on fresh material collected from the patches of scrub jungle enclosed within the Madras Christian College campus, Chennai, Tamil Nadu, India. Both sexes of H. savignyi are illustrated. H. aadi Pravalikha, Srinivasulu & Srinivasulu, 2014 is synonymized with H. savignyi Lucas, 1836.